2017
DOI: 10.1038/s41467-017-02234-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipid moieties on lipoproteins of commensal and non-commensal staphylococci induce differential immune responses

Abstract: Lipoproteins (Lpp) of Gram-positive bacteria are major players in alerting our immune system. Here, we show that the TLR2 response induced by commensal species Staphylococcus aureus and Staphylococcus epidermidis is almost ten times lower than that induced by noncommensal Staphylococcus carnosus, and this is at least partially due to their different modifications of the Lpp lipid moieties. The N terminus of the lipid moiety is acylated with a long-chain fatty acid (C17) in S. aureus and S. epidermidis, while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 77 publications
1
67
0
1
Order By: Relevance
“…Similar results were observed when the bacterial culture supernatant was used (Fig 3G and 3H) because of the loss of Tlpp expression in the supernatant of N315Δ tlpps (Fig 3F), indicating that the increased levels of IL-6 and TNFα by macrophages depended on the expression of N315 Tlpps that responded to β-lactams in a dose-dependent manner. However, the recombinant Tlpp1 purified from Escherichia coli (Fig 1C) exhibited no effect on the levels of IL-6 and TNFα by macrophages (S4 Fig), suggesting that a correctly triacylated Tlpp or a long-chain N-acylated Lpp was needed for the recognition by TLR2-TLR1 receptors to trigger immune response by macrophages [24].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were observed when the bacterial culture supernatant was used (Fig 3G and 3H) because of the loss of Tlpp expression in the supernatant of N315Δ tlpps (Fig 3F), indicating that the increased levels of IL-6 and TNFα by macrophages depended on the expression of N315 Tlpps that responded to β-lactams in a dose-dependent manner. However, the recombinant Tlpp1 purified from Escherichia coli (Fig 1C) exhibited no effect on the levels of IL-6 and TNFα by macrophages (S4 Fig), suggesting that a correctly triacylated Tlpp or a long-chain N-acylated Lpp was needed for the recognition by TLR2-TLR1 receptors to trigger immune response by macrophages [24].…”
Section: Resultsmentioning
confidence: 99%
“…The corium layer of the N315-challenged and PBS-injected mice showed an extensive inflammation with leukocyte infiltration, although abscess formation was not observed compared with that of the N315Δ tlpps -infected and PBS-injected mice. These pathological phenomena might be caused by the β-lactam-stimulated MRSA Tlpps, which stimulated the IL-6 and TNFα levels in mice (Fig 5D and 5E), thereby silencing the immune responses through granulocytic and monocyticmyeloid-derived suppressor cells induced by IL-6 [17], increasing immune cells death due to the tremendous TNFα release [24], and promoting bacterial colonization and abscess formation. Overall, these data confirmed that β-lactam-stimulated Tlpps worsened the MRSA infections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro and in vivo stimulation of HSC/HPC with Pam3CSK4 or LPS led to myeloid differentiation (82)(83)(84). Moreover, direct exposure of human and mouse HSC/HPC to TLR1/2 agonist Pam3CSK4 led to the generation of macrophages that produced lower levels of inflammatory cytokines, and reactive oxygen species (85). Further studies demonstrated that the duration and the doses of the stimulation also played an important role to determine the nature of the responses.…”
Section: Trained Immunity Memorymentioning
confidence: 97%